Apostate In Debate: Prespective Elite Muhammadiyah of East Java - Sholihul Huda (TADARUS, 2018)
Abstract This paper is the result of field research, which wants to understand and map the elite view of Muhammadiyah East Java related to apostasy phenomenon in the frame of freedom of religion. The phenomenon of apostasy is a debate among movers and activists in the Muslim and Western worlds. The debate is sharpened when it is linked to issues of religious freedom as a point in the International Declaration of Human Rights and the response of OIC States implements the death penalty for apostates. The above issues arise in Indonesia, based on data from The Wahid Institute, East Java, including areas that still often occur intolerant action related freedom of religion (Shia-Sunni case in Sampang, FPI anarchism case in Lamongan). The action of intolerance is suspected to be an extension of the apostasy-related understanding, the more beginnings of theological problem now developing in socio-theological. Extension of meaning becomes the trigger of misunderstanding in society in responding to apostasy, even lead to violence in society. This condition is very dangerous for Indonesia multicultural country. Debate on the above issues occurred among the Muhammadiyah elite in understanding and addressing the issue of religious freedom (apostasy). The background of this study was developed through a qualitative research approach with the research subjects of Muhammadiyah East Java management, data collection techniques through interview method of snowball technique and library study, inductive triangulation-data analysis, through phenomenology theory framework, social elite and knowledge sociology. The results showed that among Muhammadiyah elites in relation to the phenomenon of freedom of religion (Apostasy), there are two currents of inclusive view and exclusive views flow. Differences in view due to differences in socio-theological and socio-cultural background. In principle disagree on the death penalty for the perpetrators of apostasy and still needed the Law Defamation of religion as a framework of inter-religious relationships. Keyword: Apostasy, Perspective, Elite Muhammadiyah of East Java